Systematic Design Processes Of Hypermedia Engineering: A Case Study Of Splea-Web, - Jantan, Azrul Hazri; Sumari, Putra; Sulaiman, Shahida (2007)
Hypermedia engineering is having a rapid growth in today's Today’s engineering industry. Ongoing researches have proved that the efforts of designing and developing hypermedia applications is different compared to the conventional information system practices.